Out of this world - Gifford, Clive (London : Buster Books, 2017)
Out Of This World is jam-packed with everything children need to know about space - from facts and statistics to real-life adventures. Boys and girls can find their way around the solar system, learn if aliens really could exist and discover the origins of the universe. Entertaining and educational, this learning companion would make the perfect addition to any school child's bookshelf.
Keywords: Outer space -- Juvenile literature